Keteladanan Kepemimpinan Rasul Paulus Berdasarkan Kisah Para Rasul - Noh Asbanu (Sekolah Tinggi Teologi Erikson-Tritt Manokwari, 2022)
Leadership is an inseparable part of human life. Because Paul's example in leadership can be used as a model for leaders in carrying out their role as church leaders. Using descriptive qualitative methods with a literature study approach, it can be concluded that the role of Apostle Paul's leadership role in the Book of Acts is the first, dimension of teaching exemplary. Furthermore, the second is the exemplary dimension of the Apostle Paul's way of life for the church. Third, the dimension of faith is exemplary. And fourth, there is a dimension of exemplary love, this is the role of the leader as an actor in imitating Christian love that must always be done. Fifth, the dimension of exemplary perseverance is the role of the leader through the example of perseverance in Christian life which includes indicators of being active in serving, and steadfast in service. AbstrakKepemimpinan merupakan bagian yang tidak terpisahkan dari hidup manusia. Sebab keteladanan Paulus dalam kepemimpinan dapat dijadikan model bagi para pemimpin dalam menjalankan perannya sebagai pemimpin jemaat. Mengunakan metode kualitatif deskritif dengan pendekatan studi pustaka maka dapat disimpulkan bahwa peran keteladanan kepemimpinan rasul Paulus dalam Kitab Kisah Para Rasul adalah yang pertama, dimensi keteladanan pengajaran. Selanjutnya yang kedua adanya dimensi keteladanan cara hidup Rasul Paulus bagi jemaat ketiga, dimensi keteladanan iman. dan keempat, adanya dimensi keteladanan kasih hal ini merupakan peran pemimpin sebagai pelaku peneladanan kasih Kristiani harus selalu dilakukan. Kelima, dimensi keteladanan ketekunan adalah peran Pemimpin melalui peneladanan ketekunan hidup Kristiani yang mencakup indikator giat melayani, teguh dalam pelayanan.